2007
DOI: 10.1645/ge-1031r.1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Leishmania Braziliensis Promastigotes to Meglumine Antimoniate (Glucantime) Is Higher Than That of Other Leishmania Species and Correlates With Response to Therapy in American Tegumentary Leishmaniasis

Abstract: The first line drugs for the treatment of leishmaniasis are antimonial derivatives. Poor clinical response may be credited to factors linked to the host, the drug, or the parasite. We determined the sensitivity of Leishmania sp. promastigotes and amastigotes by counting parasites exposed to increasing concentrations of meglumine antimoniate (Glucantime). Leishmania braziliensis promastigotes were significantly more sensitive than those belonging to other species. The sensitivity of L. braziliensis isolates fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 52 publications
5
34
1
3
Order By: Relevance
“…45 Here, we observed a 94% correlation between the in vitro pentamidine results and patient outcomes. Moreover, there is concordance between in vitro promastigotes and intracellular amastigotes 46 for antimonials, when they are in the identical environment. 47 The axenic amastigote form has been suggested to be a possible alternative, because of its morphological and metabolic similarity to the intracellular macrophage amastigote form, 48 but it shares the same drawback with the promastigote form because of its inability to accumulate drugs as macrophages do.…”
Section: Discussionmentioning
confidence: 86%
“…45 Here, we observed a 94% correlation between the in vitro pentamidine results and patient outcomes. Moreover, there is concordance between in vitro promastigotes and intracellular amastigotes 46 for antimonials, when they are in the identical environment. 47 The axenic amastigote form has been suggested to be a possible alternative, because of its morphological and metabolic similarity to the intracellular macrophage amastigote form, 48 but it shares the same drawback with the promastigote form because of its inability to accumulate drugs as macrophages do.…”
Section: Discussionmentioning
confidence: 86%
“…In vitro sensitivity testing of the parasites isolated after the two intramuscular treatments and after the six intralesional injections of antimonials revealed differences between the isolates. According to AzeredoCoutinho et al 9 , L. (V.) braziliensis strains presented IC 50 values varying from 0.8 to 9.5mg/mL and the strains isolated from patients poorly responsive to therapy showed significantly higher IC 50 values than those isolated from patients who were cured after completion of the first antimonial treatment 9 . In the present study, the parasites isolated from the first biopsy were more sensitive to antimonials (0.26mg/mL) than those isolated after intralesional treatment (2.10mg/mL), a finding suggesting the development of resistance to the drug after successive cycles of treatment.…”
Section: Referênciasmentioning
confidence: 99%
“…1,4 The two main therapeutic agents, meglumine antimoniate and sodium stibogluconate, differ in terms of dosage, treatment duration and administration frequency (continuous or intermittent). [5][6][7][8][9] At the Laboratory of Leishmaniasis Surveillance, Evandro Chagas Clinical Research Institute, Oswaldo Cruz Foundation, Rio de Janeiro, Brazil, we have found continuous or intermittent intramuscular administration of meglumine antimoniate at a dose of 5 mg/kg/day to be effective and well tolerated. [10][11][12][13][14][15] The main side effects of treatment with pentavalent antimonials are myalgia, arthralgia, electrocardiographic Q-T interval prolongation, renal failure and pancreatitis accompanied by elevated lipase levels, among others.…”
Section: Introductionmentioning
confidence: 99%